2000
DOI: 10.1001/archopht.118.3.401
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fat and Fish Intake and Age-Related Maculopathy

Abstract: Main Outcome Measures: Subjects with ARM were identified from masked grading of retinal photographs. A 145itemself-administered,semiquantitativefoodfrequencyquestionnaire was completed adequately by 88.8% of participants and was used to assess intakes of dietary fat and fish. Results: A higher frequency of fish consumption was associated with decreased odds of late ARM (odds ratio for frequency of consumption more than once per week compared with less than once per month, 0.5). Subjects with higher energy-adju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
104
1
4

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 188 publications
(115 citation statements)
references
References 36 publications
6
104
1
4
Order By: Relevance
“…Foods that mainly contributed to the risk of AMD were beef, pork, and lamb; in particular, total fat and α-linolenic acid were risk factors. In contrast, DHA intake showed a modest inverse correlation with AMD risk, confirming the previously reported beneficial actions of fish intake [70]. In the same year, conflicting results were reported.…”
Section: Omega-3 and Omega-6 Pufasupporting
confidence: 76%
See 3 more Smart Citations
“…Foods that mainly contributed to the risk of AMD were beef, pork, and lamb; in particular, total fat and α-linolenic acid were risk factors. In contrast, DHA intake showed a modest inverse correlation with AMD risk, confirming the previously reported beneficial actions of fish intake [70]. In the same year, conflicting results were reported.…”
Section: Omega-3 and Omega-6 Pufasupporting
confidence: 76%
“…Smith et al [70] reported a borderline significant increase in the risk for late AMD in association with high levels of dietary cholesterol intake [70], thus confirming results reported by Mares-Perlman et al [83]. Similarly, the AREDS study described an increased likelihood of developing AMD with an increased cholesterol intake [73].…”
Section: Cholesterolsupporting
confidence: 53%
See 2 more Smart Citations
“…Few epidemiological studies are available concerning the associations of AMD with fat. In two cross-sectional studies [25,26], weekly fish consumption, which is the main source of DHA, was associated with a 50 to 60 % reduction in risk for AMD, after multivariate adjustment. In the Eye Disease Case Control Study, a high dietary intake of 6 PUFA was significantly associated with a 2 fold increased risk for exsudative AMD, after multivariate adjustment.…”
mentioning
confidence: 99%